Aktywność biochemiczna gleb w drzewostanach cisa pospolitego Taxus baccata L. w rezerwatach i lasach gospodarczych - Olszowska, Grażyna (Leśne Prace Badawcze, 2014)
The aim of these studies was to estimate the enzymatic activity and chemical properties of soils of Taxus baccata L. stands in selected forest reserves as well as in managed forest stands that do not belong to reserves. Furthermore, I compared the soil fertility of both types of forest stand using a biochemical soil quality indicator. The studies were conducted in the following reserves: „Bogdanieckie Cisy”, „Cisy Rokickie”, „Cisy Tychowskie”, „Cisy w Czarnem”, as well as in managed forest stands with the same soil and habitat type as the above-mentioned reserves. Analyses showed a lower activity of urease, asparaginase, acid phosphatase and dehydrogenase in soils of the managed forests than in soils of the reserves. The soil nutrient availability given by the total organic carbon, nitrogen, and alkaline cation content as well as soil sorption capacity were significantly lower outside the forest reserves. Chemical and biochemical parameters were used to calculate a biochemical index of soil fertility. The index was higher for soil in forest reserves than for soil in managed forest stands located outside reserves. This result held true regardless of the biochemical parameters used in the calculation. As has been shown in previous studies on protected areas with no cultivation that are largely influenced by natural processes, biochemical indices can be very useful for comparative analyses aiming at estimating soil quality or the reaction of soil to external factors, both natural and anthropogenic.